Hepatitis B virus hepatotropism is mediated by specific receptor recognition in the liver and not restricted to susceptible hosts - Schieck, Alexa; Schulze, Andreas; Gähler, Caroline; Müller, Thomas; Haberkorn, Uwe; Alexandrov, Alexander; Urban, Stephan; Mier, Walter (Hepatology, 2013)
The human hepatitis B virus (HBV) causes acute and chronic infections in humans and chimpanzees. HBV infects its hosts at minimal inoculation doses and replicates exclusively in hepatocytes. The viral determinants for the pronounced species specificity and the high efficacy to address hepatocytes in vivo are unknown. Previous findings showed that N-terminally myristoylated peptides constituting a receptor binding domain of the HBV large envelope (L)-protein block HBV entry in vitro and in vivo. Here we investigate the ability of such peptidic receptor ligands to target the liver. Injection of radioactively labeled HBVpreS-lipopeptides resulted in rapid accumulation in livers of mice, rats, and dogs but not cynomolgus monkeys. Without lipid moiety the peptide was excreted by renal filtration, indicating its possible retention through the lipid by serum factors. Organ distribution studies of 26 HBVpreS peptide variants revealed a correlation of HBV infection inhibition activity and the ability to target mouse livers. Together with complementary studies using primary hepatocytes of different species, we hypothesize that HBV hepatotropism is mediated through specific binding of the myristoylated N-terminal preS1-domain of the HBV L-protein to a hepatocyte specific receptor. Moreover, the restricted infectivity of HBV to human primates is not generally determined by the absence of this binding receptor in nonsusceptible hosts (e.g., mice) but related to postbinding step(s) (e.g., membrane fusion). Conclusion: HBVpreS-lipopeptides target to the liver. This observation has important clinical implications regarding the pharmacokinetic properties of Myrcludex B, the first entry inhibitor for HBV/HDV. In addition, this provides the basis for the application of the peptides as vehicles for hepatocyte-specific drug targeting. (HEPATOLOGY 2013)